2020
DOI: 10.1007/s10157-020-01917-5
|View full text |Cite
|
Sign up to set email alerts
|

Bardoxolone methyl: drug development for diabetic kidney disease

Abstract: Bardoxolone methyl activates the Keap1/Nrf2 system that plays an important role in defense responses against oxidative stress. Importantly, bardoxolone methyl has demonstrated increases in estimated glomerular filtration rate (eGFR) in patients with diabetic kidney disease (DKD) in clinical studies. However, an overseas Phase 3 study of bardoxolone methyl in patients with stage G4 DKD was prematurely terminated due to an increased risk for heart failure, which was considered to have been caused by early-onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 36 publications
1
43
0
1
Order By: Relevance
“…Natural bioactive compounds and their sources have been demonstrated to have kidney protective potential by activating Nrf2 in experimental CKD models [23,24]. In a recent review on clinical studies, bardoxolone methyl (CDDO-me), a semi-synthetic triterpenoid activating the Nrf2 pathway, has been reported as an effective therapeutic for diabetic kidney disease (DKD), although it has limitations in that it increases the risk of heart failure [25]. Heme oxygenase-1 (HO-1), one of the target molecules of Nrf2, attenuates the overall production of ROS through its ability to degrade heme and to produce carbon monoxide (CO), biliverdin/bilirubin, and the release of free iron.…”
Section: Introductionmentioning
confidence: 99%
“…Natural bioactive compounds and their sources have been demonstrated to have kidney protective potential by activating Nrf2 in experimental CKD models [23,24]. In a recent review on clinical studies, bardoxolone methyl (CDDO-me), a semi-synthetic triterpenoid activating the Nrf2 pathway, has been reported as an effective therapeutic for diabetic kidney disease (DKD), although it has limitations in that it increases the risk of heart failure [25]. Heme oxygenase-1 (HO-1), one of the target molecules of Nrf2, attenuates the overall production of ROS through its ability to degrade heme and to produce carbon monoxide (CO), biliverdin/bilirubin, and the release of free iron.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the most well-studied pharmacologic agent activating the NRF2 system is the drug bardoxolone methyl, which covalently binds to cysteine residues of KEAP1, allowing NRF2 to escape ubiquitination and degradation and translocate to the nucleus to induce the myriad antioxidant genes [ 53 ]. The potential beneficial effect of bardoxolone methyl on kidney function was first observed in a phase I cancer trial, where it was found to result in a statistically significant increase in estimated glomerular filtration rate (eGFR) of 26% [ 54 ].…”
Section: Nrf2 In Kidney Diseasementioning
confidence: 99%
“…Sulodexide, a glycosaminoglycan described as being able to prevent structural changes in the glomerular basement membrane, has shown positive effects on proteinuria in two small studies (60,61). Bardoxolone mathyl is demonstrated to improve inulin GFR in a Japanese phase two study, the phase 3 study results are expected early in 2022 (62). Lowering of the serum urate level with allopurinol, was however, not shown to slow the decrease in the glomerular filtration rate (GFR) in persons with type 1 diabetes and early-to-moderate diabetic nephropathy (63).…”
Section: Other Therapeutic Targets Recently Testedmentioning
confidence: 99%